Effect of biodynamic preparations on the phenolic antioxidants in potatoes with coloured-flesh. Issue 3 (3rd July 2017) - Jarienė, E.; Vaitkevičienė, N.; Danilčenko, H.; Tajner-Czopek, A.; Rytel, E.; Kucharska, A.; Sokół-Łętowska, A.; Gertchen, M.; Jeznach, M.
Abstract: The aim of this research, which was undertaken in two years (2013–2014), was to evaluate the effect of cultivars and biodynamic (BD) preparations 500 and 501 on concentrations of phenolic compounds, quantitative and qualitative anthocyanins and phenolic acids compositions, and antioxidant activity in the tubers of coloured potatoes. It was shown that when sprayed with BD preparation 501, the concentrations of total phenolic compounds in the tubers of cultivars Blue Congo and Red Emmalie was significantly higher, 20.1 and 5.4%, respectively; anthocyanins were 59.8 and 10.4% higher, respectively and antioxidant activity was approximately 1.3 times higher in the two varieties. The use of both preparations (500 and 501) had significant effects on anthocyanins accumulation in the tubers of Blue Congo and Vitelotte. However, preparation 500 had the tendency to reduce the concentrations of antioxidant compounds and antioxidant activity in tubers of all potato cultivars. The cultivar was a dominant factor affecting the phenolic antioxidants and the highest concentrations of phenolic compounds, anthocyanins and phenolic acids and the highest antioxidant activity found in the tubers of Vitelotte. Malvidin and petunidin compounds were identified as the main anthocyanins in the tubers of Blue Congo and Vitelotte, and pelargonidin compounds in Red Emmalie. The predominant phenolic acid was chlorogenic acid. A strong positive correlation was determined between antioxidant activity and the concentration of total phenolic compounds ( r  = 0.953, p  < 0.01) as well as total phenolic acids ( r  = 0.951, p  < 0.01).